2007
DOI: 10.1007/s00213-007-0812-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic alcohol exposure on dopamine uptake in rat nucleus accumbens and caudate putamen

Abstract: The DA uptake changes after chronic alcohol exposure documented here using FSCV may be associated with a compensatory response of the DA system aimed at decreasing DA signaling. Alterations in autoreceptor function may require relatively long lasting alcohol exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
5
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 56 publications
4
68
5
2
Order By: Relevance
“…This finding appears to contrast to a recent study that demonstrated an increase in dopamine clearance in the caudate putamen (Budygin et al, 2007). One potential explanation is that the increase in striatal dopamine clearance reported by Budygin et al could be mediated through a posttranslational mechanism involving alterations in DAT function and/or subcellular localization.…”
Section: Dorsal Striatumcontrasting
confidence: 91%
See 3 more Smart Citations
“…This finding appears to contrast to a recent study that demonstrated an increase in dopamine clearance in the caudate putamen (Budygin et al, 2007). One potential explanation is that the increase in striatal dopamine clearance reported by Budygin et al could be mediated through a posttranslational mechanism involving alterations in DAT function and/or subcellular localization.…”
Section: Dorsal Striatumcontrasting
confidence: 91%
“…We did not note any changes in TH expression or levels of dopamine or dopamine metabolites in the nucleus accumbens at any time point. Given the lack of temporal and spatial resolution of the neurochemical analysis we performed it is difficult to draw conclusions, but it is worth noting that this is consistent with results obtained from other groups showing no change in dopamine release properties (Budygin et al, 2007).…”
Section: Nucleus Accumbenssupporting
confidence: 83%
See 2 more Smart Citations
“…Risky decisions are those where a large but uncertain reward is favored over a smaller certain reward, a process thought to be mediated by the ventral striatum (6,7). Like virtually all drugs of abuse, alcohol alters dopamine transmission within the ventral striatum, which is a primary target of midbrain dopamine neurons (8,9). Phasic increases in dopamine transmission are evoked by rewarding outcomes and associated cues (10,11), both of which have been shown to scale with the magnitude and the probability of reward (12,13).…”
mentioning
confidence: 99%